Why do STEM immigrants do better in one country than another? - Garnett Picot; Feng Hou (IZA World of Labor, 2019)
Canada, the US, and most Western countries are looking to STEM (science, technology, engineering, and mathematics) immigrants to boost innovation and economic growth. Canada in particular has welcomed many STEM immigrants over the past quarter of a century. In the US, there is an ongoing debate about whether the H–1B visa program is being used effectively to attract more STEM immigrants. Interestingly, significant differences exist between the two countries in earnings and likely the innovation activity of highly educated immigrants, which highlights the likely role of immigration policy in determining such outcomes.
Keywords: J15; J61; 330; STEM skills; immigrant selection; US-Canada differences